Summary of Hygiene Management of Food Management Areas in the Bajoe Port Area, Bone Regency - Jumardi; Hujemiati; Darma; Fitriadi; Nirmawati Darwis (PT FORMOSA CENDEKIA GLOBAL, 2024)
In accordance with Order Number of the Minister of Health. The 2023 Environmental Health TPP is a place for food processing from raw materials to finished food. Therefore, to improve health, it is necessary to monitor TPP, especially in port areas, because a lot of human activity occurs at ports. The aim of TPP monitoring is to improve the quality of food and drinks and avoid the risk of poisoning and diseases such as diarrhea. This research is observational and based on a cross-sectional study, and the research was conducted from July to September 2023 at 16 TPPs currently operating in the Bajoe port area, Bone Regency. The variables examined in this research include location and building, sanitary conditions, kitchen, dining room and food storage area, ingredients and ready-to-eat food, food processing, food storage and ready-to-eat food, food service, equipment and labor. The total score is used when evaluating this variable. It is the sum of all ratings for each variable with a minimum value of 700. Based on the research results, of the 16 TPPs studied, there were 3 TPPs (18.75%) that did not meet hygiene requirements and 13 TPPs (81.25%) that met hygiene requirements. The conclusion of this research is that although many TPPs meet the requirements, there is still a need to improve sanitation conditions at TPPs and provide hygiene training for food handlers in the Bajoe Harbor area, Bone Regency.